2017
DOI: 10.1080/13102818.2017.1286950
|View full text |Cite
|
Sign up to set email alerts
|

Bacillusspecies as versatile weapons for plant pathogens: a review

Abstract: Plant pathogens are the main threat for profitable agricultural productivity. Currently, chemicalbased pesticides are thought to be an effective and reliable agricultural management measure for controlling pests. Chemical pesticides are highly effective and convenient to use but they are a potential threat for the environment and all kinds of life on earth. Therefore, the use of biological control agents for the management of plant pathogens is considered as a safer and sustainable strategy for safe and profit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
314
0
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(384 citation statements)
references
References 131 publications
8
314
0
22
Order By: Relevance
“…Biocontrol products protect plants against pathogens via diverse mechanisms such as direct antagonistic effect and/or activation of plant defences (Landy et al , ; Perazzolli et al , ; Shafi et al , ). They have various origins, including more or less purified plant extracts (Krzyzaniak et al , ) as well as living non‐pathogenic microorganisms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Biocontrol products protect plants against pathogens via diverse mechanisms such as direct antagonistic effect and/or activation of plant defences (Landy et al , ; Perazzolli et al , ; Shafi et al , ). They have various origins, including more or less purified plant extracts (Krzyzaniak et al , ) as well as living non‐pathogenic microorganisms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the article of Glick () provides a solid introduction to mechanisms that are related to biofertilization, improved growth and plant tolerance to disease and environmental stress. Other work has focused on Bacillus isolates (Shafi et al ., ) or the lesser studied beneficial microbes with biocontrol potential, such as Streptomyces (Rey and Dumas, ; Viaene et al ., ). Rarely does a beneficial effect on plant health correlate with only one microbial phenotype: interactions between plants and their beneficial bacteria have developed with degrees of redundancy and interdependence at the molecular level, as evidenced in this article, thus providing robust efficacy in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Estas enzimas son responsables de la degradación de los principales polisacáridos que conforma la pared celular de hongos, mediante la hidrólisis de sus enlaces glucosídicos (Figura 5). Actualmente, existen diversos estudios científicos que reportan el papel de estas enzimas en la actividad antifúngica in vitro obtenidas de cepas del género Bacillus (Kishore et al, 2005;Liu et al, 2010;Shafi et al, 2017). Por ejemplo, Yan et al (2011) demostraron el papel de una quitinasa en el control de Rhizoctonia solani por B. subtilis SL-13, evaluando la actividad inhibitoria de la enzima purificada y confrontada contra dicho patógeno.…”
Section: Producción De Enzimas Líticasunclassified
“…These enzymes are responsible for the degradation of the main polysaccharides that make up the cell wall of the fungi, by the hydrolysis of their glycosidic bonds ( Figure 5). There are currently diverse scientific studies that report the role of these enzymes in the in vitro antifungal activities obtained from strains of the Bacillus genus (Kishore et al, 2005;Shafi et al, 2017). For example, Yan et al (2011) demonstrated the role a chitinase in the control of Rhizoctonia solani by B. subtilis SL-13, evaluating the inhibitory activity of the purified enzyme, confronted with this pathogen.…”
Section: Producción De Enzimas Líticasmentioning
confidence: 99%